Effectiveness of homologous and heterologous booster doses for an inactivated SARS-CoV-2 vaccine: a large-scale prospective cohort study. Issue 6 (June 2022) - Jara, Alejandro; Undurraga, Eduardo A; Zubizarreta, José R; González, Cecilia; Pizarro, Alejandra; Acevedo, Johanna; Leo, Katherinne; Paredes, Fabio; Bralic, Tomás; Vergara, Verónica; Mosso, Marcelo; Leon, Francisco; et al.
Summary: Background: Several countries have authorised or begun using a booster vaccine dose against COVID-19. Policy makers urgently need evidence of the effectiveness of additional vaccine doses and its clinical spectrum for individuals with complete primary immunisation schedules, particularly in countries where the primary schedule used inactivated SARS-CoV-2 vaccines. Methods: Using individual-level data, we evaluated a prospective, observational, national-level cohort of individuals (aged ≥16 years) affiliated with the Fondo Nacional de Salud insurance programme in Chile, to assess the effectiveness of CoronaVac (Sinovac Biotech), AZD1222 (Oxford-AstraZeneca), or BNT162b2 (Pfizer-BioNTech) vaccine boosters in individuals who had completed a primary immunisation schedule with CoronaVac, compared with unvaccinated individuals. Individuals administered vaccines from Feb 2, 2021, to the prespecified study end date of Nov 10, 2021, were evaluated; we excluded individuals with a probable or confirmed SARS-CoV-2 infection (RT-PCR or antigen test) on or before Feb 2, 2021, and individuals who had received at least one dose of any COVID-19 vaccine before Feb 2, 2021. We estimated the vaccine effectiveness of booster doses against laboratory-confirmed symptomatic COVID-19 (symptomatic COVID-19) cases and COVID-19 outcomes (hospitalisation, admission to the intensive care unit [ICU], and death We used inverse probability-weighted and stratified survival regression models to estimate hazard ratios, accounting for time-varying vaccination status and adjusting for relevant demographic, socioeconomic, and clinical confounders. We estimated the change in hazard from unvaccinated status to vaccinated status associated with the primary immunisation series and a booster vaccine. Findings: 11 174 257 individuals were eligible for this study, among whom 4 127 546 completed a primary immunisation schedule (two doses) with CoronaVac and received a booster dose during the study period. 1 921 340 (46·5%) participants received an AZD1222 booster, 2 019 260 (48·9%) received a BNT162b2 booster, and 186 946 (4·5%) received a homologous booster with CoronaVac. We calculated an adjusted vaccine effectiveness (weighted stratified Cox model) in preventing symptomatic COVID-19 of 78·8% (95% CI 76·8–80·6) for a three-dose schedule with CoronaVac, 96·5% (96·2–96·7) for a BNT162b2 booster, and 93·2% (92·9–93·6) for an AZD1222 booster. The adjusted vaccine effectiveness against COVID-19-related hospitalisation, ICU admission, and death was 86·3% (83·7–88·5), 92·2% (88·7–94·6), and 86·7% (80·5–91·0) for a homologous CoronaVac booster, 96·1% (95·3–96·9), 96·2% (94·6–97·3), and 96·8% (93·9–98·3) for a BNT162b2 booster, and 97·7% (97·3–98·0), 98·9% (98·5–99·2), and 98·1% (97·3–98·6) for an AZD1222 booster. Interpretation: Our results suggest that a homologous or heterologous booster dose for individuals with a complete primary vaccination schedule with CoronaVac provides a high level of protection against COVID-19, including severe disease and death. Heterologous boosters showed higher vaccine effectiveness than a homologous booster for all outcomes, providing additional support for a mix-and-match approach. Funding: Agencia Nacional de Investigación y Desarrollo through the Fondo Nacional de Desarrollo Científico y Tecnológico, Millennium Science Initiative Program, and Fondo de Financiamiento de Centros de Investigación en Áreas Prioritarias.